PERJANJIAN KERJASAMA BONGKAR MUAT KAPAL ANTARA PEMILIK BARANG DENGAN PERUSAHAAN BONGKAR MUAT (STUDI PERJANJIAN PT. SENTANA ADIDAYA PRATAMA DAN PT. BHANDA GHARA REKSA PERSERO MEDAN) - ERIKA GRACIA S. (PREMISE LAW JURNAL, 2015)
Loading and unloading is one of the processes of import activities in fertilizers; it is a part of the important link of NPK fertilizer production of PT Sentana Adidaya Pratama. Without sufficient raw materials, the process of productivity cannot run punctually so that it will affect the distribution of NPK fertilizers to end-customers such as estates and other agricultural sectors. The importance of mutual agreement in loading and loading is a written contract for the parties concerned who agree on providing and receiving employment in loading and unloading of raw materials at Belawan harbor. The process of making the contract began with making pre-contract, the negotiation between the parties concerned which was then embodied in a contract through its articles, followed by the post-contract in which they fulfill their duties according to the agreement in the contract The conclusion of the research was that so far the balance between the right and the obligation has not been sufficiently carried out. Therefore, the parties concerned should pay more attention to the content of the contract and to all factors which are related to loading and unloading activities so any problem which arises in the field can be settled without any interpretation which can harm one of the parties in order to avoid any default. Therefore, ship loading and unloading should be implemented well, fast, and correctly and should cut down on cost as minimal as possible so that work performance and work outcome, which are righteous and satisfactory, can be accepted by each party Keywords: Mutual Agreement in Loading and Unloading, Balance of Duties